EFFECTS OF CARBARYL AND METHYL PARATHION ON BIMODAL RESPIRATION IN TADPOLES OF RANA TIGRINA (DAUD) (COMMON FROG) - Sampath K; Kennedy I J J; James R (Tropical Life Sciences Research, 2007)
Sublethal effects of carbaryl (CA) and methyl parathion (MP) on bimodal pattern of respiration were studied in Rana tigrina tadpoles as a function of developmental stages. The rate of aquatic respiration of tadpoles was decreased with an increase in stage from I to IV in the control and pesticide exposed tadpoles; however, the aerial respiration showed the reversed trend and it indicates the shifting of the mode of respiration from aquatic to aerial during the development of tadpoles. CA caused a decline of aquatic respiration in IV stage while MP decreased the aquatic respiration from II stage onwards and it may be due to avoidance and to minimize the gill damage by pesticide contaminated water. The results obtained for total respiration were similar to those of aquatic respiration. A stage dependent change in the percentage of aerial/aquatic respiration was observed in control and pesticide exposed tadpoles. For instance, the aquatic respiration of control tadpoles was 96.2% in I stage and it gradually reduced to 93.8%, 82.6% and 67.8% in II, III and IV stages respectively. The aerial respiration showed the opposite trend in all the experimental tadpoles. The highest concentration of MP reduced the aerial respiration by 8% compared to control tadpoles in II stage and this reduction was 17 and 16% in III and IV stages respectively. Similar trend was also obtained in tadpoles exposed to CA but the level of reduction of aerial respiration was less than those exposed to MP. This suggests that, MP is more toxic than CA and shifting of respiration from aquatic to aerial was quick due to the pesticide stress. Kesan separa maut carbaryl (CA) dan methyl parathion (MP) ke atas corak respirasi dwimod dalam berudu Rana tigrina sebagai fungsi peringkat perkembangan telah dikaji. Kadar respirasi akuatik berudu menurun dengan peningkatan peringkat dari I hingga IV dalam berudu kawalan dan berudu yang didedahkan kepada pestisid. Walau bagaimanapun, respirasi udara menunjukkan trend yang berlawanan dan ini menunjukkan pertukaran mod daripada respirasi akuatik kepada respirasi udara semasa perkembangan berudu. CA menyebabkan penurunan respirasi akuatik dalam peringkat IV manakala MP mengurangkan respirasi akuatik dari peringkat II dan ke atas. Ini mungkin bertujuan untuk mengelakkan dan meminimumkan kerosakan insang oleh air yang dicemari pestisid. Keputusan yang didapati untuk jumlah respirasi adalah hampir sama dengan respirasi akuatik. Perubahan yang bergantung kepada peringkat dalam peratusan respirasi udara/akuatik diperhatikan dalam berudu kawalan dan berudu yang terdedah kepada pestisid. Sebagai contoh, peratusan respirasi akuatik berudu kawalan ialah 96.2% dalam peringkat I dan semakin berkurang kepada 93.8%, 82.6% dan 67.8% masing-masing dalam peringkat II, III dan IV. Respirasi udara menunjukkan trend bertentangan dalam semua berudu kajian. Kepekatan MP tertinggi mengurangkan respirasi udara sebanyak 8% berbanding berudu kawalan dalam peringkat II dan pengurangan ini ialah sebanyak 17% dan 16% masing-masing dalam peringkat III dan IV. Trend serupa juga didapati dalam berudu yang terdedah kepada CA tetapi tahap penurunan respirasi udara adalah kurang daripada berudu yang terdedah kepada MP. Ini menunjukkan bahawa MP adalah lebih toksik daripada CA dan pertukaran respirasi akuatik kepada respirasi udara yang pantas adalah disebabkan oleh tekanan pestisid.